Need to review sanitary interventions promoted by the government for women in Peru - Romero-Albino, Zoila Olga (2020)
The main health interventions for health promotion and disease prevention that should be performed in women in the Peruvian health system are described. A review of normative technical documents and the recommendations of the main organizations for worldwide prevention was carried out. The prevention activities included physical activity, healthy eating, tobacco counseling, immunizations; In addition, the main screening for women, such as depression, violence, cardiovascular risk, cervical cytology, mammography, colon cancer, are detailed; and within the spectrum of quaternary prevention, interventions that have not shown evidence of benefit to women are detailed. The health interventions that are offered from the Peruvian health system for women, being merely focused on reproductive aspects, lose the conception of integrality that should prevail for the maintenance of health. In that sense, it is proposed to develop strategies that not only have evidence, but also know how to respond to the needs of women in the Peruvian context.